Studi Perubahan Garis Pantai di Teluk Penyu, Cilacap, Jawa Tengah Menggunakan Citra Sentinel-1 dan Sentinel-2 - Hanisa, Azhar Muhammad; As-syakur, Abd. Rahman; Karang, I Wayan Gede Astawa (Journal of Marine Research and Technology, 2024)
The coastline is defined as the location where water and land contact at any given time. Coastline change is considered as one of the most dynamic processes in coastal areas and is an indication of coastal accretion and erosion. The process of accretion and erosion can cause beach conditions to become unbalanced and even damaged. Cilacap Regency has a coastline of approximately 80 km which is directly adjacent to the Indian Ocean. The coast of Cilacap experienced changes in coastline which tended to be high from 1999-2008. For this reason, research has been carried out regarding coastline changes in Penyu Bay using remote sensing. The data used are Sentinel-1 and Sentinel-2 satellite images for 2016 and 2021. The analysis of shoreline changes uses the Digital Shoreline Analysis System (DSAS). The results of an analysis of shoreline changes in Penyu Bay from 2016 to 2021 show an average accretion of 1,278.49 m2 at Sentinel-1. While Sentinel-2 shows an average accretion of 2,917.68 m2. The average rate of line change per year on Sentinel-1 is 1 m/year with an indication of accretion and Sentinel-2 is 1,11 m/year with an indication of erosion. Accuracy test with Root Mean Square Error shows that Sentinel-1 is 36.80 m and Sentinel-2 is 15.43 m. Sentinel-1 has an accuracy value (CE90) of 55.84 m in class 2 with a scale of 1:100,000, while Sentinel-2 is 23.41 m in class 2 with a scale of 1:50,000.